Ischemic Priapism Associated with Glucose-6-phosphate Dehydrogenase Deficiency: A Case Report - Noor Nabi Junejo; Muhammad Humza Kamal; Shahid Aquil; Joseph Kunju Mathew (Oman Medical Journal)
Ischemic priapism is a male urologic emergency. Most cases have been linked to genetic conditions such as sickle cell disease and (much more rarely) glucose-6-phosphate dehydrogenase deficiency, and the use of certain drugs. Here, we report the case of a 34-year-old male who was a known case of the recurrent ischemic type of priapism, which was relieved by penile aspiration. Genetic investigation revealed that the patient had glucose-6-phosphate dehydrogenase.